Jeerasnidhi Lecture - Emerging opportunities for globalising Indian wheat - NAGARAJAN, S. (Indian Phytopathology, 2002)
India ranks second in the world in terms of wheat production and area of wheat grown. Each year wheat production in India reaches a new high. However, it is argued that if India is to become a permanent part of the global wheat grain trade then thecost of cultivation must be reduced whilst maintaining the yield. The effects of increasing the production efficiency and controlling wheat rusts (Puccinia spp.) and breeding for resistance to karnal bunt (Tilletia indica) are discussed.